Effect of Sacha Inchi Oil Press-Cake (Plukenetia volubilis L.) on Physicochemical and Sensory Properties of Reduced-Fat Chicken Patties (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study analyzed the proximate composition of Sacha inchi oil press-cake (SIOPC) and its effects on the physicochemical and sensory properties of chicken patties. Five formulations were prepared: a control (F0) with 0% SIOPC and 10% fat, and four variations—F1 (2.5% SIOPC + 7.5% fat), F2 (5% SIOPC + 5% fat), F3 (7.5% SIOPC + 2.5% fat), and F4 (10% SIOPC + 0% fat). Proximate analysis of SIOPC revealed a remarkable protein (54.20%) and fat (22.87%) contents. Moreover, the addition of SIOPC in chicken patties significantly increased the ash content, while reducing the fat level (p
Keywords: Sacha inchi oil press-cake (SIOPC); Fat replacement; Reduced-fat chicken patties; Physicochemical properties; Sensory evaluation